Determinants of Utilization of Free Maternity Services Among Women of Reproductive Age Between 15 To 49 Years Attending Health Facilities in Homa-Bay County, Kenya - Okumu, Wistone Churchil (JOOUST, 2022)
Free maternity services (FMS) is the offering of medical and obstetric care to pregnant women without any financial cost. Complications related to pregnancy are a major reproductive health problem that lead to disability and increased maternal deaths. Free maternity was introduced in Kenya in 2013 with a focus of achieving 100% utilization of the service and reducing high mortality rate. Homa-Bay County had a low percentage of 54% deliveries taking place in health facilities within the county as compared with the national average of 61% skilled deliveries. The main objective of this study was to establish determinants of utilization of free maternity services among women of reproductive age (15-49 years) attending health facilities in Homa-Bay County. The main research question was; what were the determinants of utilization of free maternity services among women of reproductive age (15-49 years) attending health facilities in Homa-Bay County. Descriptive cross-sectional study design was applied to establish the determinants for utilization of free maternity services among women of reproductive age (15-49 years) attending health facilities in Homa-Bay County. Homa-Bay County has a skilled delivery target of 11,812 per month and this formed the basis from which the sample size was identified. Random sampling techniques was used to identify 421 respondents who were mothers attending maternity services clinics from 12 health facilities involved in the study. In identifying the 12 facilities out of 309 health facilities in Homa-Bay County, purposive sampling technique was used to pick all the 8 sub-county hospitals and 4 health centers randomly selected. The study utilized quantitative and qualitative methods of data collection which included structured questionnaires for mothers attending maternity services, Focused Group Discussion (FGD) guide for 7-13 mothers identified in 4 health centers and 8 Key Informant Interview (KII) guide for the 8 Sub-county Hospital incharges. The data collected was analyzed using Statistical Package for Social Scientists (SPSS) version 23 software. Analysis methods were; factor analysis and regression analyses methods for quantitative data to determine the relationship and associations among the variables. Qualitative data was analyzed through content analysis by conducting thematic analysis. This study achieved response rate 94% (396/421) with 54% (213/396) mothers who were interviewed aged between 20 years and 29 years. The mean age of the mothers was 26.4 years. Results showed that; age of the mothers was insignificant in utilization of free maternity services. This could be as a result of better literacy levels and therefore most mothers only considered the quality of service as a factor of utilization. Further analysis using logistics regression revealed that the respondents who agreed with the need for a well-equipped health facility with good sanitation system were 0.37 times (OR 0.37, p = 0.03) likely to reuse FMS. Distance was insignificant in utilization as long as the facility was well-equipped and adequately staffed. This study recommends that the County Government of Homa-Bay should improve on maternity infrastructure, staffing and sanitation system of health facilities to achieve better utilization of FMS in Homa-Bay County. In conclusion, utilization of FMS is as a result of amalgamation of several factors which relates to the experience and quality of service a mother gets in a health facility.
Keywords: Free Maternity; Health Science; Reproductive Health; Women